Geometer's Sketchpad: Does it Clarify Theorems and Postulates for Geometry Students? - Chomskis, Candace A. (Valdosta State University, 2006)
The purpose of this action research study was to examine the effect of Geometer's Sketchpad, a software program for geometry instruction, on students' achievement and attitudes toward geometry and to examine a teacher's experiences while utilizing the software program. One high school geometry class, consisting of 22 students, was involved in the study during 90-minute class sessions over a 6-day period. The classroom teacher incorporated Geometer's Sketchpad into a geometry unit on circles to help students understand theorems and postulates. Findings from mathematics tests indicated that students' achievement of knowledge and skills regarding theorems and postulates for the study of circles increased. Students' attitudes toward mathematics improved as indicated by data from the attitude survey, peer/teacher observations, and student interviews. In addition, the teacher's journal provided data to support the continued use of Geometer's Sketchpad for geometry instruction.
Keywords: Geometer's Sketchpad; geometry instruction; theorems and postulates; Educational technology; Teaching--Aids and devices; Computer-assisted instruction